DISRUPTIVE ASPECTS OF THE CANADIAN INFORMATION SPACE - Ahmed Al-Rawi (The Journal of Intelligence, Conflict and Warfare)
On November 19, 2024, Professor Ahmed Al-Rawi presented Disruptive Aspects of the Canadian Information Space for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed revolved around how disruptive information encompasses verified false information with the potential to distort scientific or societal consensus. Wealth elites, political figures, media outlets, and disguised state actors are major contributors, using disruptive information to influence democratic trust and societal stability. This contributes to social fragmentation and radicalization to violence, as seen in cases like the Quebec Mosque shooter, who was influenced by far-right conspiracy theorists.